Critical Thinking Skills and Their Association with Stress Coping Strategies in the Students of Arak University of Medical Sciences Iran - Mahboobeh Najafianzadeh; Mahboobeh Khorsandi; Adeleh Mobarak Abadi (Kerman University of Medical Sciences, 2014)
Background & Objective: Critical thinking skills are among the skills that have been recognized for the 21st century human being by UNESCO On the other hand stress plays an important role in success and excessive stress can decrease students ability to learn and progress This study was performed to evaluate critical thinking skills and their association with stress coping strategies in the students of Arak University of Medical Sciences Iran   Methods: In this analytical crosssectional study 100 medical students were selected through stratified sampling SPSS software was used to analyze the data collected via a demographic checklist WatsonGlaser Critical Thinking Appraisal (WGCTA)and Ways of Coping Questionnaire (Lazarus and Folkman)   Results: The mean total score of critical thinking skills was 3732 ± 571 which was categorized as weak Moreover the mean score of stress coping strategies was 9095 ± 188 There was no significant correlation between the two mean scores There was only a weak significant correlation between avoidance with interpretation and responsibility with rationalization (P < 005)   Conclusion: The mean score of critical thinking skills of our participants did not differ significantly from that of other similar domestic studies but was unsatisfactory when compared to foreign studies This shows the necessity of the education of the critical thinking skills in the national education system The insignificant correlation between critical thinking and stress coping strategies could be the result of the questionnaire used and students wrong estimation of their critical thinking skills and coping strategies